Revision of the first therocephalian, Theriognathus Owen (Therapsida: Whaitsiidae), and implications for cranial ontogeny and allometry in nonmammaliaform eutheriodonts. (15th January 2016) - Huttenlocker, Adam K.; Abdala, Fernando
Abstract: Historically, the whaitsiid therocephalian Theriognathus Owen was one of the earliest described nonmammalian therapsids, its morphology helping to link phylogenetically the Paleozoic synapsids of North America and southern Africa to their mammalian successors. However, decades of taxonomic over-splitting and superficial descriptions obscured the morphologic diversity of the genus, hindering its utility as a study system for the evolution of synapsid cranial function as well as its biostratigraphic significance in the Late Permian of southern Africa. Here, we revise the status and provenance of all the known specimens of Theriognathus from South Africa, Tanzania, and Zambia. We present both qualitative and quantitative support for the presence of a single morphospecies as proposed by some authors. Proportional differences in skulls that were previously ascribed to different morphotypes (' Aneugomphius, ' ' Notosollasia, ' ' Moschorhynchus, ' and ' Whaitsia ') are largely size-related and allometric trends are considered here in the context of jaw function and prey prehension. Our results suggest that the single species, Theriognathus microps, represented one of the most abundant Late Permian therocephalians in southern Africa and is consequently a potentially useful biostratigraphic marker for the upper Cistecephalus -lower Dicynodon Assemblage Zone transition (i.e., late Wuchiapingian). The wide range of preserved sizes in conjunction with recent paleohistological evidence supports that individuals spent much of their lives in an actively-growing, subadult phase. Later Dicynodon Assemblage Zone records (e.g., upper Balfour Formation) are unconfirmed as the genus was likely replaced by other theriodont predators (e.g., Moschorhinus ) leading up to the Permo-Triassic boundary in the Karoo Basin of South Africa.